Analysis of Ascaris lumbricoides Infection with Total Ig E Levels in Elementary School Children of Lifuleo Village, East Kupang District - Meliance Bria; Honey Donuarta (International Journal of Health and Social Behavior, 2024)
Worm infections are a health concern in Indonesia and all other tropical nations. A number of species, including roundworms (Ascaris lumbricoides), whipworms (Trichuris trichiura), hookworms (Hookworms), Necator americanus, Ancylostoma duodenale, and Strongyloides stercoralis, are members of the Soil Transmitted Helminth nematodes. Children in elementary school are among the age groups most vulnerable to Ascaris lumbricoides. Without a clean and healthy lifestyle, an Ascaris lumbricoides infection might have major repercussions. Research on the correlation between Ascaris lumbricoides infection and total immunoglobulin E levels in primary school students is therefore required. This study uses a cross-sectional, observational analytical design. Children at Lifuleo Village's elementary schools served as the research subjects. The ECLIA method was used to assess total immunoglobulin E levels, and the Kato-Katz method was used to diagnose Ascaris lumbricoides infection under a microscope. An aberrant total immunoglobulin E level of 12.5% was observed in 42.5% of Ascaris lumbricoides eggs, according to the examination results.